2017
DOI: 10.1111/cas.13221
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II study of nab‐paclitaxel as first‐line chemotherapy in patients with HER2‐negative metastatic breast cancer

Abstract: Weekly administration of nanoparticle albumin‐bound paclitaxel (nab‐paclitaxel) has been shown to be a safe and effective treatment for metastatic breast cancer (MBC) in clinical studies. We conducted a multicenter, randomized, open‐label phase II study to compare the efficacy and safety of weekly nab‐paclitaxel and docetaxel in Japanese patients with human epidermal growth factor receptor 2‐negative MBC. The primary endpoint was progression‐free survival (PFS). Patients were randomized to receive nab‐paclitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…There is no evidence that paclitaxel agents (solvent based or nanoparticle bound) are less effective than docetaxel; on the contrary, nab-paclitaxel demonstrated improved PFS compared with docetaxel in a prospective randomised trial [8]. Nanoparticle albumin-bound (nab)-paclitaxel appears to offer similar efficacy to docetaxel, with less frequent neutropenia but more frequent sensory neuropathy [9,10]. A single-arm study (N ¼ 51) evaluating weekly paclitaxel combined with trastuzumab and pertuzumab as first-or second-line therapy reported median PFS of 25.7 months and median OS of 33 months [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that paclitaxel agents (solvent based or nanoparticle bound) are less effective than docetaxel; on the contrary, nab-paclitaxel demonstrated improved PFS compared with docetaxel in a prospective randomised trial [8]. Nanoparticle albumin-bound (nab)-paclitaxel appears to offer similar efficacy to docetaxel, with less frequent neutropenia but more frequent sensory neuropathy [9,10]. A single-arm study (N ¼ 51) evaluating weekly paclitaxel combined with trastuzumab and pertuzumab as first-or second-line therapy reported median PFS of 25.7 months and median OS of 33 months [11].…”
Section: Introductionmentioning
confidence: 99%
“…Search results. After screening 1,902 studies chosen from electronic databases and manual searches, we finally included six eligible randomized trials [2][3][4][5][6]10 for this meta-analysis ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The other 3 trials 2,3,10 included both chemotherapy-naive patients and pretreated patients. By reviewing original studies, we found that two trials excluded patients if they received adjuvant chemotherapy with taxanes (sb-paclitaxel or docetaxel) 12 months prior to study enrollment 2,3 , and another trial only included patients who had no history of chemotherapy after confirmation of metastasis 10 . We concluded that these 3 trials would not be any different from the trials with chemotherapy-naive patients.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of eight studies [10][11][12][13][14][15][16][17] which fulfilled our criteria were included in this study. We did not found any difference in efficacy of nab-paclitaxel over paclitaxel (12 months progression free survival-RR FE = 0.86, 95%CI= 0.77-0.97, p= 0.02, I 2 = 25.07%; 24 months progression free survival-RR FE = 0.86, 95% CI= 0.64-1.16, p= 0.34, I 2 = 0%; and 3 years survival-RR FE = 1.20, 95%CI= 0.92-1.56, p= 0.16, I 2 = 37.55%) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%